2014
DOI: 10.1021/cm5030553
|View full text |Cite
|
Sign up to set email alerts
|

Iron Pyrite Nanocrystal Inks: Solvothermal Synthesis, Digestive Ripening, and Reaction Mechanism

Abstract: Colloidal iron pyrite nanocrystals (or FeS 2 NC inks) are desirable as active materials in lithium ion batteries and photovoltaics and are particularly suitable for large-scale, roll-to-roll deposition or inkjet printing. However, to date, FeS 2 NC inks have only been synthesized using the hot-injection technique, which requires air-free conditions and may not be desirable at an industrial scale. Here, we report the synthesis of monodisperse, colloidal, spherical, and phase-pure FeS 2 NCs of 5.5 ± 0.3 nm in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 79 publications
0
11
0
1
Order By: Relevance
“…The monodisperse, colloidal, spherical, and phase‐pure FeS 2 NCs with the size of 5.5 ± 0.3 nm in diameter were synthesised using single source precursor iron diethyldithiocarbamate via post digestive ripening process by Yoder et al . They proposed mechanism of two acid‐catalysed steps for decomposition of the ligand that provided quantum mechanically based insight into the reaction for both hydrothermal and solvothermal reactions (Figure ).…”
Section: Nanocrystalline Pyritementioning
confidence: 99%
“…The monodisperse, colloidal, spherical, and phase‐pure FeS 2 NCs with the size of 5.5 ± 0.3 nm in diameter were synthesised using single source precursor iron diethyldithiocarbamate via post digestive ripening process by Yoder et al . They proposed mechanism of two acid‐catalysed steps for decomposition of the ligand that provided quantum mechanically based insight into the reaction for both hydrothermal and solvothermal reactions (Figure ).…”
Section: Nanocrystalline Pyritementioning
confidence: 99%
“…Jagirdar 等 [119,120] 利用消化熟化法合成了 Cu 和 Zn 等金属单分散纳米粒子, 然后经过共消化熟化得到了 Cu@ZnO 的核壳结构; Yang 等 [121] 把溶剂热法合成的多 分散 FeS 2 纳米晶(7.4±1.4 nm)经过消化熟化后获得了 FeS 2 纳米晶单分散体系(5.5±0.3 nm); Viswanatha 等 [33] 研究发现, 在油酸和油胺存在下, 经 200 ℃热处理得到 大尺寸的 FeCoS 2 纳米片, 然后再升温到 300 ℃, 可以 转变为 9 nm 的高度单分散的球状纳米晶.…”
Section: 其他纳米粒子合成unclassified
“…XRD pattern showed that water and dimethylformamide both produced phase‐pure face‐centered cubic FeS 2 (Fig. ) . Iron sulfide nanosheets were also prepared by pyrolyzing the above mentioned precursors (Figs (a) and (c)) in OLA.…”
Section: Synthesis Of Iron Chalcogenides From Single Source Precursorsmentioning
confidence: 99%
“…Non‐toxicity, environmental friendliness, ability to produce electricity and abundance of iron and sulfur help to maintain a clean environment and enhance the importance of iron sulfides . Controlling the ratio of iron and sulfur in iron sulfides is a difficult challenge due to the presence of reducible ferric and oxidizable sulfide ions .…”
Section: Synthesis Of Iron Chalcogenides From Single Source Precursorsmentioning
confidence: 99%
See 1 more Smart Citation